Induction of sustained remission in early inflammatory arthritis with the combination of infliximab plus methotrexate: the DINORA trial - Stamm, Tanja Alexandra; Machold, Klaus Peter; Aletaha, Daniel; Alasti, Farideh; Lipsky, Peter; Pisetsky, David; Landewe, Robert; Van Der Heijde, Desiree; Sepriano, Alexandre; Aringer, Martin; Boumpas, Dimitri; Burmester, Gerd; et al. (Arthritis Research & Therapy, 2018)
BACKGROUND: In the present study, we explored the effects of immediate induction therapy with the anti-tumour necrosis factor (TNF)α antibody infliximab (IFX) plus methotrexate (MTX) compared with MTX alone and with placebo (PL) in patients with very early inflammatory arthritis. METHODS: In an investigator-initiated, double-blind, randomised, placebo-controlled, multi-centre trial (ISRCTN21272423, http://www.isrctn.com/ISRCTN21272423 ), patients with synovitis of 12 weeks duration in at least two joints underwent 1 year of treatment with IFX in combination with MTX, MTX monotherapy, or PL randomised in a 2:2:1 ratio. The primary endpoint was clinical remission after 1 year (sustained for at least two consecutive visits 8 weeks apart) with remission defined as no swollen joints, 0-2 tender joints, and an acute-phase reactant within the normal range. RESULTS: Ninety patients participated in the present study. At week 54 (primary endpoint), 32% of the patients in the IFX + MTX group achieved sustained remission compared with 14% on MTX alone and 0% on PL. This difference (p < 0.05 over all three groups) was statistically significant for IFX + MTX vs PL (p < 0.05), but not for IFX + MTX vs MTX (p = 0.10), nor for MTX vs PL (p = 0.31). Remission was maintained during the second year on no therapy in 75% of the IFX + MTX patients compared with 20% of the MTX-only patients. CONCLUSIONS: These results indicate that patients with early arthritis can benefit from induction therapy with anti-TNF plus MTX compared with MTX alone, suggesting that intensive treatment can alter the disease evolution. TRIAL REGISTRATION: The trial was registered at http://www.isrctn.com/ISRCTN21272423 on 4 October 2007 (date applied)/12 December 2007 (date assigned). The first patient was included on 24 October 2007.
EVALuna2:34478